A two year retrospective study on outcome of forceps delivery – rejuvenating a dying art - Philip, Nina; Dhar, Tapasya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The obstetric forceps was designed to assist the extraction of the fetal head and 10% of all deliveries in the western world are accomplished by either vacuum or forceps. Forceps helps in avoiding Caesarean sections and can help in reducing the increase in the number of Caesarean sections. The aim of the study was to evaluate the maternal and neonatal outcome in a tertiary care hospital over a period of two years. Methods: This study was a retrospective observational study conducted over a period of two years from 1st July 2013 to 30th June 2015 in the labour ward of Christian Medical College and Hospital, Ludhiana. All operative vaginal deliveries conducted on singleton fetus in cephalic presentation were included in the study after applying the exclusion criteria. Maternal demographic data, various indicators for operative vaginal delivery and neonatal outcome were recorded. Results: A total of 2920 deliveries took place in the study period of which 156 cases (5.34%) were forceps delivery. The mean age of the patients was 26.2 years. The numbers of primigravida were 92 and multigravida was 64. Low mid cavity and outlet forceps was applied in 67 and 89 patients respectively. The most common indication for application of forceps was fetal distress (56.4%). Maternal morbidity was found in 36 women. Most of the babies were appropriate for gestational age (61.53%). Only 10.25% of the babies had low APGAR score <5 and required NICU care. Conclusions: The obstetric forceps is an effective instrument that may avoid unnecessary Caesarean sections and its complications.